"I Have Been a Sojourner in a Foreign Land": A Qualitative Inquiry on the Psychological Experiences of International Students Enrolled in a Christian University. Issue 4 (December 2021) - Moh, Sarah-Ann; Kim, Paul Youngbin; Geil, Dalton; Ryu, Sung Hun
International students make up 5.5% of all university students in the United States. In addition, international students consist of approximately 4% of the student population in Christian higher education. Although there is a significant number of international students enrolled in faith-based institutions, this population remains underrepresented in multicultural psychological literature. Thus, applying the intrapersonal-interpersonal-spiritual framework, we interviewed 15 international students from a Christian university to investigate their unique and shared experiences with the general international student population in the United States. The Consensual Qualitative Research method (CQR) was employed, and seven principal domains were identified: (a) religiousness, (b) reactions toward international students, (c) social support and acceptance, (d) hopes and expectations, (e) cultural adaptation, (f) cultural differences, and (g) international student identity. Similar themes to those present in the existing international student literature were established, but differential themes related to religiousness were discovered as well. Implications for Christian campuses are discussed.